Teritorialisasi Pengembangan Ekonomi di Wilayah Val De Saone, Lyon, Perancis Sebagai Implikasi Diciptakannya Undang-Undang Chevenement - Waskitaningsih, Novida (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Cooperation between regions in France (intercommunalité) has been known since 1890. Laws bringing a big influence on the development of cooperation between regions is The Chevènement Act 1999. This law permits the implementation of territorialisation of economic development by Urban Community (Communauté Urbaine) of Grand Lyon in Val de Saône, Lyon. We examine how the territorialisation process of economic development in Val de Saône as the implication of the creation of The Chevènement Act. As a result, we found that the territorialisation is a kind of adaptation to the Chevènement Act enforcement related to the authority of Urban Community of Grand Lyon and Association between regions of Saône Mont d’Or (Syndicat de Communes Saône Mont d’Or) in economic development in Val de Saône. Territorialisation is characterized by the consensus and the signing of the development contract concerning the role division between Urban Community of Grand Lyon, which has a new authority in intervening the economic development in local and metropolitan level, and Association Between Regions of Saône Mont d’Or, which has the same authority in intervening the economic development in local level of Val de Saône.